2010
DOI: 10.1111/j.2042-3306.2010.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between radiological and magnetic resonance imaging lesions in the distal border of the navicular bone with particular reference to distal border fragments and osseous cyst‐like lesions

Abstract: Fragments observed radiologically are likely to be associated with other pathological abnormalities of the distal border of the navicular bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…This finding is clearly visible on MRI scans, and it has been shown that horses with distal border fragments are more likely to be lame than horses without . The presence of distal border fragments can be predicted by radiographic lucency of the lateral or medial angles of the distal border of the bone . However, it also clearly documented that sound horses can have distal border fragmentation .…”
mentioning
confidence: 96%
“…This finding is clearly visible on MRI scans, and it has been shown that horses with distal border fragments are more likely to be lame than horses without . The presence of distal border fragments can be predicted by radiographic lucency of the lateral or medial angles of the distal border of the bone . However, it also clearly documented that sound horses can have distal border fragmentation .…”
mentioning
confidence: 96%
“…There are few studies in equine veterinary medicine comparing CR and/or DR and conventional film-screen radiography (Hertsch and others 1988, Bindeus and others 2002, Moorman and others 2009, Biggi and Dyson 2010), but CR was found to be significantly superior to conventional radiographic techniques in the diagnostic quality of caudocranial projections of the equine stifle (Bindeus and others 2002) and for the detection of large-size and high-grade distal border fragments of the navicular bone (Biggi and Dyson 2010). …”
mentioning
confidence: 99%
“…Unfortunately, these studies are also the most difficult to conduct, mainly due to the fact that in addition to your imaging findings you need to have clarity over the clinical signs as well as a confirmed outcome. At the moment the ‘gold standard’ for diagnosis is most commonly the post mortem examination, ideally including histopathology (although I do wonder if this is always true, especially in relation to MRI and scintigraphy that provide information about function rather than morphology which histopathology may not be able to show, see for example . Dr Sue Dyson and her group at the Animal Health Trust in Newmarket have conducted pioneering work in this area over recent decades and she has continued this with her paper in the current issue on the comparison between MRI and histological findings in the navicular bone in horses .…”
mentioning
confidence: 99%
“…A good example of this is changes in the distal border of the navicular bone. The clinical importance of distal border fragments was evaluated with MRI 2 years ago and the radiographic appearance of synovial invaginations has been further investigated by comparing it with computed tomography as published in this issue by Claerhoudt and co‐workers .…”
mentioning
confidence: 99%